Role of microvascular invasion in early recurrence of hepatocellular carcinoma after liver resection: A literature review - Zhi-Hong Zhang; Chuang Jiang; Ze-Yuan Qiang; Yi-Fan Zhou; Jun Ji; Yong Zeng; Ji-Wei Huang (Asian Journal of Surgery, 2024)
Summary: Hepatectomy is widely considered a potential treatment for hepatocellular carcinoma (HCC). Unfortunately, one-third of HCC patients have tumor recurrence within 2 years after surgery (early recurrence), accounting for more than 60% of all recurrence patients. Early recurrence is associated with a worse prognosis. Previous studies have shown that microvascular invasion (MVI) is one of the key factors for early recurrence and poor prognosis in patients with HCC after surgery. This paper reviews the latest literature and summarizes the predictors of MVI, the correlation between MVI and early recurrence, the identification of suspicious nodules or subclinical lesions, and the treatment strategies for MVI-positive HCC. The aim is to explore the management of patients with MVI-positive HCC.